Good Governance Sebagai Upaya Meningkatkan Partisipasi Masyarakat dalam Pembangunan di Indonesia - Anneke Zehan Puspita Sari; Naomi Glori Natalia; Ratu Wulan Nur Cahya; Rudiana Rudiana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Participation of the community is a key factor in sustainable development. In order to achieve this, the Indonesian government needs to ensure that the community can actively participate in the development process. One of the efforts that can be made by the government to encourage community participation in development is by applying the principles of Good Governance. Good Governance has four main pillars, namely transparency, accountability, participation, and responsiveness. This research shows that the application of Good Governance principles can increase community participation in development in Indonesia. In addition, Good Governance strategies such as transparency and accountability, community participation in decision-making, improving the capacity of government officials, and improving the quality of public services can be applied to ensure active community participation in development. The Indonesian government needs to increase efforts to encourage community participation in development. One of the efforts that can be made is to consistently and transparently apply the principles of Good Governance. The government also needs to provide complete and easily understood information access to the community, as well as provide opportunities for the community to give input and opinions in the decision-making process. Improving the capacity of government officials is also necessary so that they have adequate competence in carrying out their duties and responsibilities. The government must also ensure that the public services provided are of quality and satisfactory to the community. By implementing these efforts, it is hoped that community participation in development can increase and create more sustainable and equitable development for all people in Indonesia.